DAKWAH PENCERAHAN Pemikiran dan Aktivitas Dakwah Muhammadiyah Zaman Kekinian - Ichwansyah Tampubolon (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2016)
The concept of Dakwah Pencerahan (the enlightening Islamic preaching) is a new  model of Islamic preaching which is constructed and held by Muhammadiyah in order to revitalize and revivalize it`s activities on da`wah in the contemporary era. This concept of da`wah not only can be understood as a critical thought for conventional thought of Islamic preaching, but also can be appreciated as an innovative da`wa forcreation the real solution of the problems of Islamic societies in their socio-cultural and religious life in the context of Indonesian Moslem and universal humanity. Hence, this concept is based subtantially and integrally on the Islamic principles, Indonesian local wisdoms, and universal humanity values.